Pengaruh risiko usaha terhadap profitabilitas pada bank umum swasta nasional devisa - Syania Dita Cahyani; Herizon Herizon (STIE Perbanas Surabaya, 2019)
The purposes of this study are analyzes the simultaneously and partially effect of LDR, IPR, NPL, APB, IRR, PDN, BOPO, FBIR to ROA in Bank Umum Swasta Nasional Devisa. The sample of this study consisted of four banks: Bank CIMB Niaga, Bank Permata, Bank Pan Indonesia, and Maybank. This study used secondary data taken from the financial statements of Bank Umum Swasta Nasional Devisa. The bank period from the first quarter of 2013 to the second quarter of 2018. The technique of analyzing data is descriptive analysis and used linear regression analysis, F table, t table. The result of this study indicate that analyzing LDR, IPR, NPL, APB, IRR, PDN, BOPO, FBIR simultaneously have a significant effect on ROA in Bank Umum Swasta Nasional Devisa. Partial LDR, IPR and APB have unsignificant negative effect on ROA in Bank Umum Swasta Nasional Devisa. NPL and IRR partially have unsignificant positive effect on ROA in Bank Umum Swasta Nasional Devisa. PDN and BOPO partially have significant negative effect on ROA in Bank Umum Swasta Nasional Devisa. FBIR partially has significant positive effect on ROA in Bank Umum Swasta Nasional Devisa.